DESAIN SISTEM PENGENDALIAN INTERNAL DALAM RANGKA MENJAGA DAN MENCAPAI EFEKTIVITAS PENGGUNAAN KAS KECIL PADA CV NUANSA JINGGA - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
The purpose of this study is to analyze the petty cash internal control system in CV Nuansa Jingga based on the problems retaled to petty cash, which is the most problem is the over budget on entity’s petty cash. Source of data collected from CV Nuansa Jingga both primary and secondary. This research tries to make the design of petty cash internal control system to reduce the over budget, and implemented to entity’s management. The result of the study is that CV Nuansa Jingga has already implemented the design of petty cash internal control system as much 74,16%.